Tinjauan Literatur: Analisis Penggunaan Sistem Informasi Manajemen Puskesmas: - - Cipta Ningrat, Rossita; Kurnianto, Andreas; Masruchi (Jurnal Kesehatan, 2024)
The Community Health Center Information System is a program that provides information about all health facilities at the first facility level, namely the Community Health Center. SIMPUS (The Community Health Center Information System) is useful for looking at the needs and capabilities of community health centres in managing, processing and preserving data. In its implementation at Community Health Centers, not all Community Health Centers can run SIMPUS well. The biggest obstacle to implementing SIMPUS is the lack of training provided to the human resources personnel who will use it.  This research aims to determine and analyze the implementation of SIMPUS use at Community Health Centers. The research method used was a literature review of several journal articles. The data found resulted from a literature review of articles based on Google Scholar using the keywords SIMPUS and the Puskesmas information system with a journal publication time limit of 2019 to 2024. There were 12 articles that met the criteria. Based on the results of the analysis, it was found that several obstacles experienced by SIMPUS in each Community Health Center were not in accordance with Standard Operating Procedures, such as network problems and training for human resources. By finding obstacles in the implementation of SIMPUS, it will be possible to improve the implementation of SIMPUS in the future.